(untitled) (Biological Sciences - PJSIR, 2004)
Aqueous extracts of various parts of leaf, stem and root of common purslane were evaluated alone or in combination with NaC1 to see their effects on germination and seedlings growth of rice. Leaf and stem extracts have no effects on germination, while the root extract alongwith 0.4% NaC1 decreased the rice seed germination. However, length of both shoot and root were significantly decreased under extracts alone or in combination with NaC1 levels. Root growth was affected more than the shoot irrespective of the treatments.